Estilos de socialización parental y afrontamiento en estudiantes de la unidad educativa “Vicente Anda Aguirre”. Riobamba, Octubre 2017 – Marzo 2018 - Tingo Ortiz, William Alexis (2018)
The objective of this research was to determine the styles of parental socialization and coping strategies in the students of the Educational Unit "Vicente Anda Aguirre" of the city of Riobamba. The study was carried out under a non-experimental design, of correlational descriptive type. The sample was intentional non-probabilistic, was composed of 78 students, 14 and 15 years of age corresponding to the tenth year of Basic General Education parallel A and B. The techniques used for data collection were psychometric tests and the instruments used were The Adolescent Parental Socialization Scale (ESPA 29) and the adolescent coping scale (ACS), the results found that the predominant parental socialization style is authoritative for both fathers and mothers, followed in this style we find the indulgent with a high index that results from the sum of both percentages of the parents. In relation to coping we have that the main strategies with the highest percentage are: Strive and Succeed (Es), the Physical Distraction (Fi) strategy. and the strategy Look at the Positive (Po), which belong to the group of productive strategies; In addition, significant correlations were found between the two proposed variables: parental socialization styles and coping.